Tubicolixa Theil & Felder 2020, n. gen. - Theil, Emma Palacios; Felder, Darryl L. (Zenodo, 2020)
Genus Tubicolixa n. gen. urn:lsid:zoobank.org:act: 00ADBC20-FD16-4594-B5FB-A7DE037E3E8F TYPE SPECIES. — Tubicolixa chaetopterana (Stimpson, 1860) n. comb. [ Pinnixa ]. DIAGNOSIS. — Carapace uneven, regions clearly limited by depressions, some surfaces heavily pubescent, especially margins; cardiac region with transverse crest, not extending entirely across carapace; branchial regions with granulate or serrated edges. Third maxilliped with ischiomerus subtrapezoidal; propodus and dactylus longer than carpus, shorter than ischiomerus, elongate; dactylus inserting near base of propodus, reaching beyond end of propodus. Chelipeds strongly developed, setose, with shortened or deflexed fixed finger, in some cases sexual dimorphism. First two ambulatory legs (P 2 and P 3) slender, third and fourth (P 4 and P 5) stouter; relative lengths P4> P3> P2> P5. Male pleon tapering toward end, telson subsemicircular; first pleonal somite lacking gonopodal plate between gonopods. ETYMOLOGY. — Named Tubicolixa in recognition of the group apparent preference for polychaete tubes as a habitat. Gender feminine. ADDITIONAL SPECIES. — Tubicolixa brevipollex (Rathbun, 1898) n. comb. [ Pinnixa ]; Tubicolixa rapax (Bouvier, 1917) n. comb. [ Pinnixa ]. MATERIAL EXAMINED. — In addition to the material included in the phylogenetic analyses (Table 1) the following material was available for examination: Tubicolixa chaetopterana n. comb. — ULLZ 12480 (Beaufort, NC, USA), ULLZ 4452 (2), ULLZ 4561 (2), ULLZ 5553 (2), ULLZ 6429, ULLZ 7395, ULLZ 7400, ULLZ 10286, ULLZ 14005 (2), ULLZ 14008 (6), ULLZ 14110, ULLZ 14907 (4), ULLZ 14911, ULLZ 17925 (Fort Pierce, FL, USA), ULLZ 14916 (Peanut Is, FL, USA), ULLZ 5542 (7) (Florida Keys, USA), MNHN-IU-2017-9370, ULLZ 17456 (2) (Tampa Bay, FL, USA), ULLZ 14080 (2) (St. Mark’s lighthouse, FL, USA), ULLZ 14996, ULLZ 14997 (2) (St. Joseph’s State Park, FL, USA), ULLZ 8638 (2), ULLZ 14875 (3) (St. Andrew’s Bay, FL, USA), ULLZ 14024 (2) (Perdido Key Beach, FL, USA), ULLZ 8657 (7) (offshore Mississippi, USA), ULLZ 5552 (2) (Isles Dernieres, LA, USA), ULLZ 14832 (Bryan Mound, TX), ULLZ 2597 (3) (Padre Island, TX, USA). Tubicolixa rapax n. comb. — ULLZ 14115 (Ubatuba, Brazil). REMARKS Genetic and morphological differences between specimens of T. chaetopterana (Stimpson, 1860) n. comb. from Venezuela and Belize and those from the Gulf of Mexico and North Atlantic coasts at minimum suggest population structure within this species. This taxon may represent a species complex, similar to that observed for some of the species of Scleroplax , with different morphotypes at the species and/or population level likely adapted to different habitats and/or hosts. However, most preserved samples available to us at present do not represent sequence quality materials. Additional studies with larger and more broadly representative sample sizes based on markers with resolution at the population level should be undertaken, along with more detailed collection information regarding habitat and hosts. Additional samples of T. chaetopterana n. comb. from Belize should further clarify the identification of that juvenile specimen, once at least a 12S sequence for can be obtained. The holotypes of Pinnixa brevipollex Rathbun, 1898 (USNM 21593, near La Plata estuary, Argentina) and Pinnixa rapax Bouvier, 1917 (MCZ 10997, Gulf of San Matías, Argentina) require further study and comparison, along with molecular and morphological studies based on contemporary samples representing their putatively separate populations. These species have been suggested to be synonyms, but the holotypes remain to be compared (Fenucci 1975; Bezerra et al. 2006). Some authors suggest there are differences in the male pleon (Righi 1967), but the allegedly junior synonym P. rapax is still considered a valid species (Ng et al. 2008). This group may represent yet another species complex, and we elect to for now continue their treatment as separate taxa. PROVISIONAL MORPHOLOGICAL KEY TO AMERICAN GENERA OF PINNIXINAE ŠTEVČIĆ, 2005 The present key must be regarded as provisional since many couplets require mature males, and these are not known or available for all species of each genus. Thus, it cannot be ruled out that exceptions to some of the applied characters may occur. It also includes one generic level taxon that remains to be named. 1. Carapace cardiac region posterior surface crossed from side to side by single sharp continuous ridge (most commonly associated with burrowing callianassid ghost shrimps, western Atlantic and eastern Pacific) (see Manning and Felder, 1989 for quality illustrations and examples).......................... Austinixa Heard & Manning, 1997 — Carapace cardiac ridge, if present, not crossing the surface of carapace completely (most commonly associated with burrowing worms, mollusks, and upogebiid mud shrimps)................................................................. 2 2. Maxilliped 3 dactylus large and heavy, as long as or longer than propodus, oriented in a wide angle, sometimes near perpendicular relative to it (Fig. 2 H), or (for Glassella costaricana ) dactylus strongly reduced, inserted subdistally (Fig. 2 G); carapace ovate, punctate, regions usually poorly marked; external surface of chela palm often bearing longitudinal ridges or lines of granules, sometimes setose (Fig. 2 E); male pleon often with fused segments, telson broader than preceding segment (Fig. 2 I).......................................................................... 3 — Maxilliped 3 dactylus reaching to or slightly beyond the end of the propodus, dactylus and propodus elongated, oriented parallel or nearly parallel to each other (Fig. 2 C, L, P, T, X); carapace varies; male pleon without fused segments, telson shape varied...................................................................................................................... 5 3. Male pleon with telson short, broader than long, semiellipsoid (Fig. 2 I); carapace punctate (western Atlantic, eastern Pacific)...................................................................................... Glassella Campos & Wicksten, 1997 — Male pleon with telson semicircular, inflated, nearly as long as broad; carapace smooth, forming angle at lateral edges.......................................................................................... (“ Pinnixa sp.” ULLZ 13337, ULLZ 14141) 4. Mature cheliped fingers not strongly deflected from longitudinal axis of propodus, fixed finger not deflected ventrally from longitudinal axis (Fig. 2 B, S); carapace convex, regions poorly marked (Fig. 2 A, R).............. 5 — Mature cheliped fixed finger deflected ventrally from longitudinal axis of propodus, often shortened (Fig. 2 K, O, W); carapace varied................................................................................................................................ 6 5. Cheliped fixed finger not conspicuously shortened relative to palm, chelae with little sexual dimorphism, ridge on fixed finger continuing partially on palm (Fig. 2 B); carapace lateral angles setose (Fig. 2 A); male pleon with telson semiellipsoid (Fig. 2 D) (western Atlantic)........................................................... Pinnixa White, 1846 — Cheliped fixed finger somewhat shortened relative to palm, male cheliped strong, female cheliped feeble, in some cases line of tubercles on chela palm, but no conspicuous ridge (Fig. 2 S); carapace lateral angles rounded, with no patches of setae (Fig. 2 R); male pleon with telson semicircular (Fig. 2 U) (northeastern Pacific coasts, Alaska to Mexico)................................................................................................... Scleroplax Rathbun, 1983 6. Male pleon with telson elongate, more than twice as wide as long (Fig. 2 Q); mature cheliped fixed finger strongly reduced, replaced by a spiniform angle of propodus, sharp tooth at the base of dactylus (Fig. 2 O); carapace anterolateral margins without tuberculate ridge, each with single lobiform tubercle just anterior to lateral extreme (Fig. 2 N) (western Atlantic)..................................................................................................... Sayixa n. gen. — Male pleon with telson semicircular or semitriangular, not more than twice as wide as long (Fig. 2 M, Y); mature cheliped fixed finger varied, if spiniform, with no additional sharp large tooth at the base of dactylus (Fig. 2 K, W); carapace anterolateral margins often with tuberculate ridge, no conspicuous tubercle near lateral extreme (Fig. 2 J, V).................................................................................................................................................. 7 7. Ambulatory legs (P 2– P 4) subequal, slender, compressed, dactyli long and slender, nearly as long as propodi; carapace regions clearly defined, branchial region crossed by tuberculate ridge (Fig. 2 J); male pleon with telson subtriangular (Fig. 2 M) (western Atlantic, eastern Pacific)................................................ Rathbunixa n. gen. — First ambulatory legs (P 2 and P 3) slender, next two pairs (P 4 and P 5) swollen, dactyli strong, shorter than propodi; carapace regions clearly defined, branchial region with no conspicuous tuberculate ridge (Fig. 2 V); male pleon with telson semicircular (Fig. 2 Y) (western Atlantic)................................................. Tubicolixa n. gen. PROVISIONAL MORPHOLOGICAL KEY TO AMERICAN GENERA OF PINNIXINAE ŠTEVČIĆ, 2005 The present key must be regarded as provisional since many couplets require mature males, and these are not known or available for all species of each genus. Thus, it cannot be ruled out that exceptions to some of the applied characters may occur. It also includes one generic level taxon that remains to be named. 1. Carapace cardiac region posterior surface crossed from side to side by single sharp continuous ridge (most commonly associated with burrowing callianassid ghost shrimps, western Atlantic and eastern Pacific) (see Manning and Felder, 1989 for quality illustrations and examples).......................... Austinixa Heard & Manning, 1997 — Carapace cardiac ridge, if present, not crossing the surface of carapace completely (most commonly associated with burrowing worms, mollusks, and upogebiid mud shrimps)................................................................. 2 2. Maxilliped 3 dactylus large and heavy, as long as or longer than propodus, oriented in a wide angle, sometimes near perpendicular relative to it (Fig. 2 H), or (for Glassella costaricana ) dactylus strongly reduced, inserted subdistally (Fig. 2 G); carapace ovate, punctate, regions usually poorly marked; external surface of chela palm often bearing longitudinal ridges or lines of granules, sometimes setose (Fig. 2 E); male pleon often with fused segments, telson broader than preceding segment (Fig. 2 I).......................................................................... 3 — Maxilliped 3 dactylus reaching to or slightly beyond the end of the propodus, dactylus and propodus elongated, oriented parallel or nearly parallel to each other (Fig. 2 C, L, P, T, X); carapace varies; male pleon without fused segments, telson shape varied...................................................................................................................... 5 3. Male pleon with telson short, broader than long, semiellipsoid (Fig. 2 I); carapace punctate (western Atlantic, eastern Pacific)...................................................................................... Glassella Campos & Wicksten, 1997 — Male pleon with telson semicircular, inflated, nearly as long as broad; carapace smooth, forming angle at lateral edges.......................................................................................... (“ Pinnixa sp.” ULLZ 13337, ULLZ 14141) 4. Mature cheliped fingers not strongly deflected from longitudinal axis of propodus, fixed finger not deflected ventrally from longitudinal axis (Fig. 2 B, S); carapace convex, regions poorly marked (Fig. 2 A, R).............. 5 — Mature cheliped fixed finger deflected ventrally from longitudinal axis of propodus, often shortened (Fig. 2 K, O, W); carapace varied................................................................................................................................ 6 5. Cheliped fixed finger not conspicuously shortened relative to palm, chelae with little sexual dimorphism, ridge on fixed finger continuing partially on palm (Fig. 2 B); carapace lateral angles setose (Fig. 2 A); male pleon with telson semiellipsoid (Fig. 2 D) (western Atlantic)........................................................... Pinnixa White, 1846 — Cheliped fixed finger somewhat shortened relative to palm, male cheliped strong, female cheliped feeble, in some cases line of tubercles on chela palm, but no conspicuous ridge (Fig. 2 S); carapace lateral angles rounded, with no patches of setae (Fig. 2 R); male pleon with telson semicircular (Fig. 2 U) (northeastern Pacific coasts, Alaska to Mexico)................................................................................................... Scleroplax Rathbun, 1983 6. Male pleon with telson elongate, more than twice as wide as long (Fig. 2 Q); mature cheliped fixed finger strongly reduced, replaced by a spiniform angle of propodus, sharp tooth at the base of dactylus (Fig. 2 O); carapace anterolateral margins without tuberculate ridge, each with single lobiform tubercle just anterior to lateral extreme (Fig. 2 N) (western Atlantic)..................................................................................................... Sayixa n. gen. — Male pleon with telson semicircular or semitriangular, not more than twice as wide as long (Fig. 2 M, Y); mature cheliped fixed finger varied, if spiniform, with no additional sharp large tooth at the base of dactylus (Fig. 2 K, W); carapace anterolateral margins often with tuberculate ridge, no conspicuous tubercle near lateral extreme (Fig. 2 J, V).................................................................................................................................................. 7 7. Ambulatory legs (P 2– P 4) subequal, slender, compressed, dactyli long and slender, nearly as long as propodi; carapace regions clearly defined, branchial region crossed by tuberculate ridge (Fig. 2 J); male pleon with telson subtriangular (Fig. 2 M) (western Atlantic, eastern Pacific)................................................ Rathbunixa n. gen. — First ambulatory legs (P 2 and P 3) slender, next two pairs (P 4 and P 5) swollen, dactyli strong, shorter than propodi; carapace regions clearly defined, branchial region with no conspicuous tuberculate ridge (Fig. 2 V); male pleon with telson semicircular (Fig. 2 Y) (western Atlantic)................................................. Tubicolixa n. gen. PROVISIONAL MORPHOLOGICAL KEY TO AMERICAN GENERA OF PINNIXINAE ŠTEVČIĆ, 2005 The present key must be regarded as provisional since many couplets require mature males, and these are not known or available for all species of each genus. Thus, it cannot be ruled out that exceptions to some of the applied characters may occur. It also includes one generic level taxon that remains to be named. 1. Carapace cardiac region posterior surface crossed from side to side by single sharp continuous ridge (most commonly associated with burrowing callianassid ghost shrimps, western Atlantic and eastern Pacific) (see Manning and Felder, 1989 for quality illustrations and examples).......................... Austinixa Heard & Manning, 1997 — Carapace cardiac ridge, if present, not crossing the surface of carapace completely (most commonly associated with burrowing worms, mollusks, and upogebiid mud shrimps)................................................................. 2 2. Maxilliped 3 dactylus large and heavy, as long as or longer than propodus, oriented in a wide angle, sometimes near perpendicular relative to it (Fig. 2 H), or (for Glassella costaricana ) dactylus strongly reduced, inserted subdistally (Fig. 2 G); carapace ovate, punctate, regions usually poorly marked; external surface of chela palm often bearing longitudinal ridges or lines of granules, sometimes setose (Fig. 2 E); male pleon often with fused segments, telson broader than preceding segment (Fig. 2 I).......................................................................... 3 — Maxilliped 3 dactylus reaching to or slightly beyond the end of the propodus, dactylus and propodus elongated, oriented parallel or nearly parallel to each other (Fig. 2 C, L, P, T, X); carapace varies; male pleon without fused segments, telson shape varied...................................................................................................................... 5 3. Male pleon with telson short, broader than long, semiellipsoid (Fig. 2 I); carapace punctate (western Atlantic, eastern Pacific)...................................................................................... Glassella Campos & Wicksten, 1997 — Male pleon with telson semicircular, inflated, nearly as long as broad; carapace smooth, forming angle at lateral edges.......................................................................................... (“ Pinnixa sp.” ULLZ 13337, ULLZ 14141) 4. Mature cheliped fingers not strongly deflected from longitudinal axis of propodus, fixed finger not deflected ventrally from longitudinal axis (Fig. 2 B, S); carapace convex, regions poorly marked (Fig. 2 A, R).............. 5 — Mature cheliped fixed finger deflected ventrally from longitudinal axis of propodus, often shortened (Fig. 2 K, O, W); carapace varied................................................................................................................................ 6 5. Cheliped fixed finger not conspicuously shortened relative to palm, chelae with little sexual dimorphism, ridge on fixed finger continuing partially on palm (Fig. 2 B); carapace lateral angles setose (Fig. 2 A); male pleon with telson semiellipsoid (Fig. 2 D) (western Atlantic)........................................................... Pinnixa White, 1846 — Cheliped fixed finger somewhat shortened relative to palm, male cheliped strong, female cheliped feeble, in some cases line of tubercles on chela palm, but no conspicuous ridge (Fig. 2 S); carapace lateral angles rounded, with no patches of setae (Fig. 2 R); male pleon with telson semicircular (Fig. 2 U) (northeastern Pacific coasts, Alaska to Mexico)................................................................................................... Scleroplax Rathbun, 1983 6. Male pleon with telson elongate, more than twice as wide as long (Fig. 2 Q); mature cheliped fixed finger strongly reduced, replaced by a spiniform angle of propodus, sharp tooth at the : Published as part of Theil, Emma Palacios & Felder, Darryl L., 2020, Phylogeny of the genus Pinnixa White, 1846 (Crustacea, Brachyura, Pinnotheridae) and allies inferred from mitochondrial and nuclear molecular markers, with generic reassignment of twenty-one species, pp. 85-103 in Zoosystema 42 (6) on pages 99-100, DOI: 10.5252/zoosystema2020v42a6, http://zenodo.org/record/3695831 : {"references": ["RATHBUN M. J. 1898. - The Brachyura collected by the U. S. Fish Commission steamer Albatross on the voyage from Norfolk, Virgina, to San Francisco, California 1887 - 1888. Proceedings U. S. National Museum 21: 567 - 616, XLI-XLIV. https: // doi. org / 10.5479 / si. 00963801.21 - 1162.567", "FENUCCI J. L. 1975. - Los cangrejos de la familia Pinnotheridae del litoral argentino (Crustacea, Decapoda, Brachyura). Physis, Seccion A, Buenos Aires 34: 165 - 184.", "BEZERRA L. E. A., DE ALMEIDA A. O. & COELHO P. A. 2006. - Occurrence of the family Pinnotheridae De Haan (Crustacea, Decapoda, Brachyura) on the coast of Ceara State, Brazil. Revista Brasileira de Zoologia 23 (4): 1038 - 1043. https: // doi. org / 10.1590 / S 0101 - 81752006000400008", "RIGHI G. 1967. - Sobre alguns Decapoda do Brasil (Crustacea, Brachyura: Pinnotheridae e Parthenopidae). Papeis Avulsos de Zoologia, Sao Paulo 20: 99 - 116.", "NG P. K. L., GUINOT D. & DAVIE P. J. F. 2008. - Systema Brachyura: Part I. An annotated checklist of extant Brachyuran crabs of the world. The Raffles Bulletin of Zoology 17: 1 - 286.", "MANNING R. B. & FELDER D. L. 1989. - The Pinnixa cristata complex in the western Atlantic, with a description of two new species (Crustacea: Decapoda: Pinnotheridae). Smithsonian Contributions to Zoology 473: 1 - 26. https: // doi. org / 10.5479 / si. 00810282.473", "CAMPOS E. & WICKSTEN M. K. 1997. - A new genus for the Central American crab Pinnixa costaricana Wicksten, 1982 (Crustacea: Brachyura: Pinnotheridae). Proceedings of the Biological Society of Washington 110 (1): 69 - 73.", "WHITE A. 1846. - Notes on four new genera of Crustacea. The Annals and Magazine of Natural History [series 1] 18: 176 - 178, Plate 2, Figures 1 - 6."]}